The Effect of Hamstring Eccentric Strength and Asymmetry on Acceleration and Vertical Jump Perfor-mance in Professional Female Soccer Players - Adela Badau; Şebnem Şarvan Cengiz; Hüseyin Karesi; Batuhan Er (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The aim of this study was to investigate the relationship between eccentric hamstring muscle strength and acceleration and vertical jump in professional female soccer players. Twentieth professional female soccer players actively playing soccer participated in the study voluntarily with age (arithmetic mean±standard deviation) 18.31±5,97. The NORDBORD device was used to measure the participants' hamstring eccentric force output, the Smartspeed™ Contact Mat was used for vertical jump performance and the FUSIONSPORTS Smartspeed™ PRO photocell (Fusion Sport, Queensland, Australia) was used for 0-20m sprint performance measurements. When the relationship between eccentric hamstring strength parameters, vertical jump and sprint performance of the participants was analyzed, no significance was found. It is seen that there is a negative relationship between VJ and 0-5m at a moderate level (r=-586, p=.022) and a negative relationship between VJ and 0-20m at a high level (r=-.793, p=-.000). Since the studies examining the relationship between Hamstring Strength and Sprint performance are limited in number, it is not possible to reach a definite conclusion, more comprehensive and more studies are needed.